The Library's own intranet applications and Content Management System facilitating librarian's work and library processes - Raczyński, Rafał (Biblioteka Uniwersytecka we Wrocławiu, 2015)
The key role in computerization, apart from the aspect of equipment, is played by proper procedures and carefully matched programs. The article briefly describes two applications developed between 2008-2015 in Computerization Department and its connection to Digital Library of University of Wrocław (DLUWr). The next part of the paper is devoted to the implementation of Content Management System (CMS) to Wrocław University Library and to the factors which are decisive in choosing a specific solution. Discussed are also the main phases (milestones) of DLUWr development, and the origin together with the background of establishing Repository of University of Wrocław (RUWr) is explained. The final part includes consideration about the way of digital publications development: the author discusses the Library's 10-year experience in this matter, lists advantages and disadvantages of the centralist approach with one system of presentation in contrast to a mixed approach, the latter allowing for other sources of digital works.
Keywords: systems integration; repository; Drupal; Internet application; digitized collections inventory; central online register of correspondence; digital library